The Relationship Between the Number of Ports and Surgical Outcomes in Laparoscopic Hepatectomy. Issue 1 (February 2020) - Inoue, Yoshihiro; Kitada, Kazuya; Fujii, Kensuke; Kagota, Syuji; Tomioka, Atsushi; Yamaguchi, Toshifumi; Yokohama, Keisuke; Ohama, Hideko; Hamamoto, Hiroki; Ishii, Masatsugu; Osumi, Wataru; Tsuchimoto, Yusuke; et al.
Abstract : Introduction: Reduced port surgery (RPS) has been garnering interest as a novel minimally invasive surgery lately. Aim: The authors examined the relationship between the number of ports and surgical outcomes after laparoscopic hepatectomy (LH). Materials and Methods: Between January 2012 and April 2019, 209 patients who underwent laparoscopic partial resection and lateral sectionectomy were retrospectively analyzed with respect to operative variables and surgical outcomes. Patients were divided into 5 groups by the number of ports used. Student's t test, the χ 2 test, the likelihood-ratio test, Fisher exact test, or Mann-Whitney U test were used to analyze the data. Results: Operative duration was significantly longer in patients with a larger number of ports than in those with a smaller number of ports. Chronological pain scores according to the visual analog scale (VAS) on postoperative days 1, 2, 4, and 7 were not associated with the number of ports and wound length in the umbilical region. The frequency of using additional analgesic agents was not significantly different between the groups. VAS scores and the number of additional analgesic agents used were smaller in patients in whom non–steroidal anti-inflammatory drugs were regularly administered postoperatively than in those in whom the drug was not regularly administered postoperatively. LH had a 3.4% complication rate (Clavien-Dindo classification >IIIA); however, this was not significantly different between the groups. Conclusions: No significant difference in postoperative pain was observed between RPS and conventional methods, although operative durations were shorter with RPS. However, RPS for LH may be associated with excellent cosmetic results compared with conventional methods.